THE EFFECT OF HUSNUZHAN TRAINING ON THE QUALITY OF LIFE AMONG WOMEN WITH HYPERTENSION - Radhiatul Fitri; Siti Urbayatun; Elli Nur Hayati (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
Hypertension is one of the leading causes of heart disease, stroke, kidney disease and death. The prevalence of hypertension in women is higher than that of in men. Women suffering from hypertension potentially experience various problems that affect the quality of life. Several techniques can be used to improve the quality of life for women with hypertension such a husnuzhan training. Husnuzhan training is a kind of Islamic-Psychoreligious intervention. This study aimed to investigate the effectiveness of Husnuzhan training in improving the quality of life among women with hypertension. Twenty women with hypertension aged between 40-50 years participated in the study which employed a pretest-posttest control group design. WHOQOL-BREF instrument was used to assess the quality of life among participants. Husnuzhan Training was delivered for 4 sessions in two weeks. The data were analysed using the Wilcoxon signed-rank test and U-Mann Whitney. The result showed a significant improvement in the quality of life’s score in the experimental group when compared to the control group (Z = -3.181 & p = 0.001 (p <0.01). U-Mann Whitney test results also showed no difference in quality of life’s score in both groups at baseline phase (Z = -1.212, p = 0.226 (p> 0,05). Therefore, husnuzhan training effectively improved the quality of life in women with hypertension. Limitations of this study were discussed. Keywords: Hypertension, Quality of Life, Husnuzhan Training